COVID-19 & differential effects in twins: Insights from Placenta Pathology. (24th June 2022) - Moriarty, Kristen; Yu, Mingfu; Hussain, Naveed; Zgutka, Kinga; Sanders, M. Melinda; Harigopal, Malini; Wang, Jianhui; Wang, Xi; Hui, Pei; Liu, Chen; Sink, David; Shields, Andrea
Abstract: Introduction: COVID-19 has been associated with several adverse pregnancy outcomes, including perinatal loss. Differential effects of COVID-19 in a twin pregnancy may provide unique insights into virus-placental interactions. We present a case of perinatal loss of a female fetus with survival of the male co-twin in a pregnancy complicated by COVID-19 and premature delivery. Methods: Viral detection methods recommended by the NICHD task force were used to identify SARS-CoV-2 and its viral receptors in the placentas and fetal tissue (Antoun et al., 2020) [1] Results: Compared with the surviving twin, we found a more severe intervillous necrosis and a relatively low detection of ACE2 membranous expression in the syncytiotrophoblasts of the female twin that succumbed. Discussion: The interactions of SARS-CoV-2 and ACE2 at the maternal fetal interface within the placenta may play a significant role in perinatal loss, and the effects of fetal sex and gestational age at time of infection need to be explored further. Highlights: SARS-CoV-2 was isolated from placental and fetal tissue in a mother-twin triad. The placenta of demised twin A showed more severe intervillious necrosis. Less ACE-2 receptor expression was seen in necrotic trophoblasts of twin A. SARS-CoV-2 was concentrated to syncytiotrophoblasts in fetal tissue. Low viral load in fetal tissue likely does not cause discernible fetal changes.